Modelo de Medición, Análisis, Planeación y Programación de Capacidades en un Contexto de Múltiples Criterios de Desición - Kalenatic, Dusko; López Bello, César Amilcar; González Rodríguez, Leonardo José (Ingeniería, 2004)
This paper presents a model of capacity planning for the manufacturing companies with an approach multi-criterion, with it a theoretical support is tried to meet that adecue to different situations in which an organization can be orientating his activity, besides fixing a methodology to approach the problem of management of the capacity in an environment of multiple criteria. With the model of multiple criteria, the obtained information, it facilitates the process of analysis, programming and orientation for the make of decisions and the effective execution of the strategies of production, capacity extension planning and capacityscheduling. With the analysis, information is generates for the determination of the necks of bottle, for the projection of extension of the available and installed capacity, of the resources machine and of the labor force, possible absorption of the potential market and other indicators of management. The formulation of the models bears in mind the availability of the resource machine in a process of production for stages, in which there uses labor force of polyvalent character, of agreement to the trends in the personnel training with aptitudes to realize several functions in contraposition to the specialization of the work.